The South American Defense Council: the Building of a Community of Practice for Regional Defense - Vitelli, Marina Gisela [UNESP] (Inst Brasileiro Relacoes Int, 2017)
While the South American Defense Council has been analyzed as a security community, we argue that it is best described as an early stage community of practice, since it has successfully set in motion a regular interaction dynamic between numerous defense actors, as we demonstrate with concrete examples. We further discuss political support as a prerequisite for regional defense identity.
Keywords: Security communities; community of practice; seminar diplomacy; South America; Defense